Interobserver variability in the treatment of little finger metacarpal neck fractures. - Tosti, Rick; Ilyas, Asif M; Mellema, Jos J; Guitton, Thierry G; Ring, David (J Hand Surg Am, 2014)
PURPOSE: To address the null hypothesis that surgeons shown radiographs of little finger metacarpal neck fractures with measured fracture angulation would recommend surgery as often as surgeons shown unmarked radiographs. METHODS: Members of the Science of Variation Group, an international collaboration of fully trained orthopedic and trauma surgeons, were asked to review 20 little finger metacarpal neck fracture cases, which included a vignette and 3 high-quality radiographs. Members were then randomized to review radiographs with or without measured fracture angulation on the lateral view and select operative or nonoperative management. RESULTS: Surgeons shown radiographs with measured angulation were more likely to recommend surgery, and there was less variability among these surgeons, particularly for fractures with less angular deformity. CONCLUSIONS: Measured fracture angulation has a small but significant influence on treatment recommendations for little finger metacarpal neck fractures. TYPE OF STUDY/LEVEL OF EVIDENCE: Diagnostic III.
Keywords: Adult; Aged; Female; Finger Injuries; Fractures, Bone; Humans; Male; Metacarpus; Middle Aged; Observer Variation; Practice Patterns, Physicians'; Radiography; Random Allocation